Improving quality and outcomes of coronary artery bypass grafting procedures. (3rd May 2016) - Ferguson, T. Bruce; Buch, Ashesh N.
ABSTRACT: The evolution in the approach, clinical care and outcomes of ischemic heart disease, has been dramatic over the past decade. Optimizing medical therapy initially and throughout the care delivery process has been transformative. The addition of new physiologic data to the traditional anatomic framework for diagnosis and therapy of more extensive stable ischemic heart disease (SIHD) enables quality and outcomes improvements in this patient population overall and in the patient subsets of acute coronary syndrome and SIHD. In patients undergoing coronary artery bypass grafting (CABG), these developments have changed the objective goal of surgical revascularization over this time interval. This review discusses the opportunities for quality and outcomes improvement in CABG, in the context of SIHD overall.